2013
DOI: 10.1155/2013/959084
|View full text |Cite
|
Sign up to set email alerts
|

The −174G/C and −572G/C Interleukin 6 Promoter Gene Polymorphisms in Mexican Patients with Rheumatoid Arthritis: A Case-Control Study

Abstract: Objective. There is a lack of information about the genotype frequencies of IL-6 −174G/C and −572G/C polymorphisms in Mexicans with rheumatoid arthritis (RA). Therefore, the aim of this study was to evaluate the association of the IL-6 −174G/C and −572G/C polymorphisms in Mexican mestizo with RA. Methods. We included 137 patients with RA and 102 healthy controls. Patients were assessed for clinical characteristics. IL-6 −174G/C and −572G/C polymorphisms were genotyped using PCR-RFLP analysis. Allele and genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
0
22
2
Order By: Relevance
“…Our results were in agreement with Zavaleta-Muñiz et al, 2013 who found no significant differences in allele or genotype frequencies of this polymorphism between RA and controls. But in contrast to our results, they found that the GG genotype was the most frequently observed genotype in the Mexican mestizo population among patients with RA and healthy controls (54% and 60.8% respectively) [7]. Also, Li et al, 2014a observed no association for IL-6 −572G/C gene polymorphism and RA in Chines Han population.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results were in agreement with Zavaleta-Muñiz et al, 2013 who found no significant differences in allele or genotype frequencies of this polymorphism between RA and controls. But in contrast to our results, they found that the GG genotype was the most frequently observed genotype in the Mexican mestizo population among patients with RA and healthy controls (54% and 60.8% respectively) [7]. Also, Li et al, 2014a observed no association for IL-6 −572G/C gene polymorphism and RA in Chines Han population.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, our results were against different studies in which they found no differences in allele or genotype frequencies of IL-6 −174G/C gene polymorphism between RA and controls in a different population such as Mexican and Turkish populations [7, 8]. The controversy of results may be due to different origin or ethnicity.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…A study assessing the frequency of the -174G/C polymorphism in the IL6 gene showed that the -174G/G genotype of IL6 was more prevalent in RA compared with the CC and GC genotypes (Zavaleta-Muñiz et al, 2013). Our results are in accordance with the findings described by Gao et al (2015), who conducted a meta-analysis comparing the frequency of the IL6 gene -174G/C polymorphism in different populations with sepsis and healthy controls, where was reported that GG was the most frequent genotype in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The genotyping of the -174G/C and -572G/C polymorphisms was performed by trained personnel blinded to the patients' clinical characteristics. The genotypes were screened by an approach based on polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), and SfaNI and BsrBI restriction endonucleases were used for the -174G/C and -572G/C polymorphisms, respectively, as described elsewhere (Zavaleta-Muñiz et al, 2013). The resulting fragments were analyzed by electrophoresis on a 6% polyacrylamide gel stained with silver nitrate.…”
Section: Dna Extraction and Il6 -174g/c And -572g/c Genotypingmentioning
confidence: 99%